Comparison of heuristics for an economic lot scheduling problem with deliberated coproduction - Vidal-Carreras, Pilar I. (OmniaScience, 2018)
We built on the Economic Lot Scheduling Problem Scheduling (ELSP) literature by making some modifications in order to introduce new constraints which had not been thoroughly studied with a view to simulating specific real situations. Specifically, our aim is to propose and simulate different scheduling policies for a new ELSP variant: Deliberated Coproduction. This problem comprises a product system in an ELSP environment in which we may choose if more than one product can be produced on the machine at a given time. We expressly consider the option of coproducing two products whose demand is not substitutable. In order to draw conclusions, a simulation model and its results were developed in the article by employing modified Bomberger data which include two items that could be produced simultaneously.